2015
DOI: 10.1007/s12031-015-0696-1
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-Like Peptide-1 Strengthens the Barrier Integrity in Primary Cultures of Rat Brain Endothelial Cells Under Basal and Hyperglycemia Conditions

Abstract: The objective of the present study was to determine the effects of glucagon-like peptide-1 (GLP-1) on barrier functions and to assess the underlying mechanism using an in vitro blood-brain barrier (BBB) model comprised of a primary culture of rat brain capillary endothelial cells (RBECs). GLP-1 increased transendothelial electrical resistance and decreased the permeability of sodium fluorescein in RBECs in a dose- and time-dependent manner. The effects on these barrier functions were significantly reduced in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 43 publications
2
21
0
Order By: Relevance
“…Activated GLP‐1R can exert multifarious neuroprotective effects in Alzheimer's, Parkinson's diseases and stroke by combining with GLP‐1 or long‐acting GLP‐1R agonists. Consistent with studies showing that GLP‐1 can stabilize the integrity of the BBB, activating GLP‐1R may be one of the mechanisms by which Cb attenuated BBB impairment in TBI mice. Our results showed that Cb treatment could exert neuroprotective activity, which may be via stimulating secretion of GLP‐1 and subsequently activating GLP‐1R in the brain.…”
Section: Discussionsupporting
confidence: 83%
“…Activated GLP‐1R can exert multifarious neuroprotective effects in Alzheimer's, Parkinson's diseases and stroke by combining with GLP‐1 or long‐acting GLP‐1R agonists. Consistent with studies showing that GLP‐1 can stabilize the integrity of the BBB, activating GLP‐1R may be one of the mechanisms by which Cb attenuated BBB impairment in TBI mice. Our results showed that Cb treatment could exert neuroprotective activity, which may be via stimulating secretion of GLP‐1 and subsequently activating GLP‐1R in the brain.…”
Section: Discussionsupporting
confidence: 83%
“…Studies in db/db mice and in vitro models showed increased activation of protein kinase Cβ (PKCβ), and when treated with the selective PKCβ inhibitor LY-317615, BBB leakiness and macrophage infiltration were prevented (226, 233). Fukuda et al observed inhibition of ROS and improvement in the integrity of the BBB in hyperglycemia when treated with glucagon-like peptide 1 (GLP-1) agonist, a newer class of antidiabetic agents, suggesting this might be a BBB-protective treatment for diabetic patients (97). …”
Section: Cerebrovascular Integritymentioning
confidence: 99%
“…How GLP‐1 might decrease risk of cerebrovascular disease or improve memory is not fully understood. GLP‐1 may modulate various pathophysiological mechanisms by affecting brain glucose levels , the blood–brain barrier (BBB) or the central regulation of heart rate and blood pressure. Different GLP‐1RAs might have variable effects based on different compound structures, modes of administration and pharmacokinetics.…”
mentioning
confidence: 99%